Water-in-salt electrolytes achieve high energy densities at an ultralow-temperature for aqueous symmetrical supercapacitors. Issue 39 (26th April 2022) - Zhu, Jiajing; Sun, Yi; Gao, Jie; Qin, Zhanbin; Zhou, Yanan; Tian, Ran; Gao, Yun
Abstract : LiTFSI/H2 O water-in-salt electrolytes with different concentrations show high energy densities for capacitive charge storage at sub-zero-temperatures. Abstract : LiTFSI/H2 O water-in-salt electrolytes with different concentrations show high energy densities for capacitive charge storage at sub-zero-temperatures ( e.g. 32.23, 38.35 and 35 W h kg −1 at 0, −10 and −20 °C, which are 1.44, 1.71 and 1.56 times that of normal temperature).